Ahmed Glaucoma Valve Implantation for Uveitic Glaucoma Secondary to Behçet Disease. Issue 8 (October 2015) - Satana, Banu; Yalvac, Ilgaz S.; Sungur, Gulten; Eksioglu, Umit; Basarir, Berna; Altan, Cigdem; Duman, Sunay
<x xml:space="preserve">Abstract</x> Purpose: To evaluate outcomes of patients with uveitic glaucoma secondary to Behçet disease (BD) who underwent Ahmed glaucoma valve (AGV) implantation. Patients and Methods: A retrospective chart review of 14 eyes of 10 patients with uveitic glaucoma associated with BD who underwent AGV implantation at a tertiary referral center. Treatment success was defined as intraocular pressure (IOP) between 6 and 21 mm Hg with or without antiglaucoma medication, without further additional glaucoma surgery or loss of light perception. The main outcome measures were IOP, best-corrected visual acuity measured with Snellen charts, and number of glaucoma medications. Results: Mean duration of postoperative follow-up was 18.2±6.6 months (range, 6 to 31 mo). Of the 14 eyes, 10 (71.4%) were pseudophakic and 5 (35.7%) had primary AGV implantation without a history of previous glaucoma surgery. At the most recent follow-up visit, 13 of the 14 eyes had an IOP between 6 and 21 mm Hg. Mean IOP was significantly reduced during follow-up, as compared with preoperative values (P⩽0.005). The cumulative probability of surgical success rate was 90.9% at 18 months based on Kaplan-Meier survival analysis. The mean number of antiglaucoma medications required to achieve the desired IOP decreased from 3.4±0.5 preoperatively to 1.0±1.1 postoperatively (P⩽0.05). Visual acuity loss of >2 lines occurred in 4 eyes (28.5%) due to optic atrophy associated with retinal vasculitis. Temporary hypotony developed during follow-up in 4 eyes (28.5%) at first postoperative week. Conclusions: For the management of uveitic glaucoma associated with BD, AGV implantation is a successful method for glaucoma control but requires additional surgical interventions for high early hypotony rates.